CURRENT PROBLEMS OF COLOR CHARACTERISTICS IN MODERN ARCHITECTURE AND ARCHITECTURE - Muhammadiyev Husan Hamroqulovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article is based on the actual problems of color properties in architecture, and presents the color concepts of different eras and the period of color application to the present, and also reveals the trends of color solutions, including the influence of colors on human emotions and perception of the whole world. secret issues are covered.